If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = -1 + -5h Solving 14 = -1 + -5h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '5h' to each side of the equation. 14 + 5h = -1 + -5h + 5h Combine like terms: -5h + 5h = 0 14 + 5h = -1 + 0 14 + 5h = -1 Add '-14' to each side of the equation. 14 + -14 + 5h = -1 + -14 Combine like terms: 14 + -14 = 0 0 + 5h = -1 + -14 5h = -1 + -14 Combine like terms: -1 + -14 = -15 5h = -15 Divide each side by '5'. h = -3 Simplifying h = -3
| 4a-5=3m+7 | | 2=3x+7 | | 7-8n+4n=16-97 | | -53+10y+4=4(4y-2)-5 | | 11=7-2k | | 7(c-2)+7=2+c-9 | | -10+4k=k-2k | | 5x-3y-15=0 | | 4n-8n=18 | | -10(x-3)+28=-16-16 | | 9y^3+2=y-18y | | 0=-6(y+9) | | 6.1-3x=4.2 | | a^2-3a-54= | | 1.0-6.4x=-9.4 | | r-11-8r=29 | | 2.4-8.6x=-26.5 | | (3x+1)-(x-1)=4 | | 11y-3=15 | | x^2+2xy-8y^2=0 | | 0.9-2.01-0.39x-0.6=0.44x-16.96+0.16x-0.74 | | (3x^2+6x-3)=0 | | (3x+1)-(x-1)=2 | | 6q-1=-q-8 | | t+(t+3)(-3)=t-3 | | p=-1.555555556 | | -4(4y-9)+2(2y+9)= | | 6y-9=13y+40 | | -275(-3x-5)=-5.75(1-2x) | | x^2-12x-180=0 | | d+6=6+d | | -0.34(3x-1)=0.28(3-4x) |